ETR 300 : SP Fresh Fish Trading / Mohamad Naaim Mat Noor …. [et al.] - Mat Noor, Mohamad Naaim; Ismail, Khairul Shahrizal; Mohd Padzil, Suhardi; Kamis, Mohd Azlan; Mohamed, Azrul Hafiz (2000)
SP Fresh Fish Trading was established when all the partners were agreed to form this fresh fish business. We choose this types of business because of the demand from market which market are really need fresh fish and SP Fresh Fish Trading exist with a own new market strategy that is we put out the stinky smelling of fish whereby we cut SP Fresh Fish will start the business on 1 January 2001 after received the approval from the Business Registrar and confirmed our business registration number.